Performance evaluation of conventional and fuzzy control systems for speed control of a DC motor using positive output Luo converter. (2019) - Boutouba, Mohamed; Ougli, Abdelghani El; Tidhaf, Belkassem
Precise speed control of DC motors is an important requirement for efficient industrial automation and diverse applications fields. In this paper, a speed control of a DC motor for a photovoltaic system is proposed using fuzzy logic technique as a controller with a DC-DC converter type positive output Luo converter (POLC). POLC, one of a new generation of DC-DC converters which presents multiples advantages, is used as an intermediary between the photovoltaic source and the DC motor, in order to control the transmitted power with low power losses. Multiple classical control techniques could be used to control DC motor speed. However, in this work, a PI fuzzy logic controller (FLC) is proposed to get better pursuit, response and speed accuracy which represents important parameters to control on some industrial applications. Different system blocks are developed on MATLAB/Simulink as environment. Simulation results, using comparison between a conventional PID controller and the PI-fuzzy logic controller, demonstrate the good behaviour of the proposed system.